Preparo e caracterização morfológica, microestrutural e magnética de eletrodepósitos de NiFe e NiFeCu - Pereira, Rodrigo (2016)
This work presents the investigation of the correlation between microstructural, morphological and compositional properties with the magnetic behavior of NiFe and NiFeCu alloys. A 23 factorial design was carried out to correlate the effects of preparation variables on the NiFe and NiFeCu films properties. The studied parameters have been the deposition potential (-1,03 V and -1,10 V), deposition time (15 and 40 minutes) and temperature of bath (25 °C and 45 °C). Structural characterization was performed by X-ray diffraction (XRD) and Reitveld refinement showed the formation of the film NiFe and NiFeCu with face-centred cubic (FCC) structure with preferred orientation in the (111) direction and anisotropic cause by strain and crystallite size. The morphological characterization showed the formation of a homogeneous film with a similar grain structure of the sample prepared. The magnetic properties of the alloys were performed magnetic moment measurements as a function of magnetic field, temperature and the angle between the applied magnetic field and the sample surface. The results showed the directions of easy magnetization axis and the contribution of different types of magnetization anisotropic. The magnetic properties, saturation magnetization (MS), remanent magnetization (MR) e Curie temperature (TC), depend on the atomic amount of Ni and Fe present in alloys. Moreover, it was possible to correlate the microstructural modification (crystallite size and strain) with magnetic properties of the alloys.